PENINGKATAN HASIL BELAJAR IPA DALAM TEMA PEDULI TERHADAP LINGKUNGAN MELALUI PENDEKATAN SAINTIFIK - Sribani, Endah (Jurnal Pendidikan Dasar, 2017)
Abstract: this study aims to improve the learning results of natural science in the theme of caring for theenvironment through scientific approaches to class IV elementary school in the land of Eucalyptus 09 EastJakarta. This action research conducted in two cycles, one cycle and the second. The subject of this actionresearch is learners class IV elementary school Eucalyptus Land 09 years lessons 2016/2017. Data collectionwas done through some way i.e. observation to process data by using the observation sheet implementationassisted by collaborators. Test results of study consisting of the initial test was used as a foothold to draw up aplan of action will be implemented through the steps in the cycle in order to improve the learning results of theIPA. The results of this research show that the results of the learn IPA learners class IV elementary schoolCountry Wood 09 increased at both KI 3 or 4 with the execution applied to KI, strategies and tools.